Derivación de valores económicos de la producción de leche de bovinos en la parroquia Guaytacama utilizando funciones de beneficio. - Quelal Viana, Edison Fabricio (2022)
The genetic evaluation of dairy cattle is the fundamental pillar for a genetic improvement program, considering genealogical and phenotypic information, as well as helping to know dairy farm situation. However, in Guaytacama, small producers carry out a technician not exploitation and their decisions are based on traditional knowledge, consequently, there is a reduced profitability on given productions, mainly due to selection problems of reproducers without the genotype-environment interaction. Therefore, an evaluation of economic values on Guaytacama is carried out to small milk producers, obtaining 31 people that are linked to genetic improvement project with 107 cattle, of which 27 are milk producing cows. The animals are managed at semi-stabled herd, in a space not exceeding one hectare, with a stocking rate of 3.2 UBA. Feeding is deficient due to the size of owners' land; they can not keep this number of animals this space and they also use vacant land and buy feed, increasing the production cost per liter of milk. There is no profit value for milk production if labor hours are taken into account, since the cost of producing a liter of milk is $0.62 and sale price is $0.42. If working hours are not considered, the value of 0.13$ is obtained, generating a profitability of 0.29$ per liter of produced milk. Density is at the average value of 1.027 g/ml, a value below the normal average of 1.029 g/ml. Daily weight gain is at a value of 570 g/day, lower than normal value of 600 to 700 g/day. The selection criteria that should be applied are gain weight, milk density, daily milk production, which is in an average range of 8Kg/cow/day.